Alternatives to Aerobic Exercise Prescription in Patients with Chronic Heart Failure - Oliveira,Mayron F (2016)
Background: Exercise is essential for patients with heart failure as it leads to a reduction in morbidity and mortality as well as improved functional capacity and oxygen uptake (v̇O2). However, the need for an experienced physiologist and the cost of the exam may render the cardiopulmonary exercise test (CPET) unfeasible. Thus, the six-minute walk test (6MWT) and step test (ST) may be alternatives for exercise prescription. Objective: The aim was to correlate heart rate (HR) during the 6MWT and ST with HR at the anaerobic threshold (HRAT) and peak HR (HRP) obtained on the CPET. Methods: Eighty-three patients (58 ± 11 years) with heart failure (NYHA class II) were included and all subjects had optimized medication for at least 3 months. Evaluations involved CPET (v̇O2, HRAT, HRP), 6MWT (HR6MWT) and ST (HRST). Results: The participants exhibited severe ventricular dysfunction (ejection fraction: 31 ± 7%) and low peak v̇O2 (15.2 ± 3.1 mL.kg-1.min-1). HRP (113 ± 19 bpm) was higher than HRAT (92 ± 14 bpm; p < 0.05) and HR6MWT (94 ± 13 bpm; p < 0.05). No significant difference was found between HRP and HRST. Moreover, a strong correlation was found between HRAT and HR6MWT (r = 0.81; p < 0.0001), and between HRP and HRST (r = 0.89; p < 0.0001). Conclusion: These findings suggest that, in the absence of CPET, exercise prescription can be performed by use of 6MWT and ST, based on HR6MWT and HRST